2018
DOI: 10.5194/acp-2018-1189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling of aerosol property evolution during winter haze episodes over a megacity cluster in northern China: Roles of regional transport and heterogeneous reactions

Abstract: <p><strong>Abstract.</strong> Regional transport and heterogeneous reactions played crucial roles in haze formation over a megacity cluster centered on Beijing. In this study, the updated Nested Air Quality Prediction Model System (NAQPMS) and the HYSPLIT Lagrangian trajectory model were employed to investigate the evolution of aerosols – in terms of the number concentration, size distribution, and aging degree – in Beijing during six haze e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The composition and phase state of an inorganic aerosol system was calculated using a thermodynamic equilibrium model (ISORROPIA v1.7) (Nenes et al, 1998). Further technical details about the NAQPMS can be found in Li et al (2012, 2011) and Du et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…The composition and phase state of an inorganic aerosol system was calculated using a thermodynamic equilibrium model (ISORROPIA v1.7) (Nenes et al, 1998). Further technical details about the NAQPMS can be found in Li et al (2012, 2011) and Du et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the aging processes during the transport in the atmosphere is another reason for the increased size at high PM levels because highly polluted periods were oen found to be largely inuenced by regional transport. 54,55 As shown in Fig. S12, † the differences of OA loading between relatively clean days and moderately polluted conditions (35 mg m À3 < NR-PM 1 < 70 mg m À3 ) peaked at $300 nm, which was smaller than that between relatively cleaner days and seriously (NR-PM 1 > 70 mg m À3 ) polluted conditions ($480 nm), highlighting that particles with relatively small sizes play an important role in the formation of moderate pollution compared to severe pollution.…”
Section: Size Distributions Of Oa Factorsmentioning
confidence: 99%
“…For the rural GZB transport sector, the fraction of sulfate and nitrate largely decreased to 19 % and 11 % of PM 2.5 , respectively, consistent with lower SO 2 (3.2 ± 2.5 µg m −3 ) and NO 2 (27.8 ± 10.3 µg m −3 ) in the rural GZB transport sector, which was about half of that in the three urban transport sectors (6.3-7.3 µg m −3 for SO 2 and 44.7-51.3 µg m −3 for NO 2 ). The high fraction of sulfate in the BTH transport sector was supported by high concentrations of SO 2 and sulfate in the BTH region and central China region (Du et al, 2019;Chen et al, 2020;Li et al, 2021a;Sun et al, 2022). It was further supported by high sulfur conversion efficiency (SOR), for which the BTH transport sector showed the highest SOR of 0.58, followed by the northern China transport sector (0.52), the urban GZB transport sector (0.49) and the rural GZB transport sector (0.44) (Fig.…”
Section: Secondary Inorganic Formation During the Transportmentioning
confidence: 96%
“…Some modeling studies reported that heterogeneous chemistry during transport was identified as the dominant factor during haze episodes in megacities (Li and Han, 2016;Li et al, 2017) and were further supported by the observations. Du et al (2019) reported that the chemical transformation from SO 2 to sulfate was the major source of sulfate in Beijing. Li et al (2021b) suggested that the pollution in winter in Beijing was largely affected by regional transport, and water vapor during transport of the air mass greatly increased the SIA proportion.…”
Section: Introductionmentioning
confidence: 99%